Assessing the effects of drought stress on photosynthetic performance and physiological resistance in camphor seedling leaves - Renjie Wang; Xingxing Qin; Huibiao Pan; Dianyun Li; Xiao Xiao; Yuke Jin; Yong Wang; Huizi Liang (PLoS ONE, 2025)
The impact of seasonal short-term drought on plant physiology and resilience is crucial for conservation and management strategies. This study investigated drought stress effects on growth, photosynthetic capacity, and physiological responses of Camphor (Cinnamomum camphora) seedlings in Guangxi province, China. Fertilized potted plants underwent continuous drought treatments to assess varying water supply effects. Treatments included normal water supply (CK), light drought (D1), moderate drought (D2), and severe drought (D3). Physiological indicators including net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), and intercellular CO2 concentration (Ci) were measured. Additionally, the stomatal limitation value (Ls) was calculated using the formula Ls = 1-Ci/Ca, and water use efficiency (WUE) was computed as Pn/Tr. Furthermore, parameters such as PIABS (Performance Index based on absorbed light energy), WK (the ratio of variable fluorescence FK at the K point to the amplitude FO-FJ), VJ (the ratio of variable fluorescence FJ at the J point to the amplitude FO-FP), ΔI/I0 (the relative amplitude of the 820 nm light absorption curve), superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and malondialdehyde (MDA) were measured to evaluate the impact of drought stress on various physiological processes and antioxidant enzyme activities. Results showed significant decreases in base diameter growth (GD) and seedling height growth (GH) with increasing drought stress. Notably, moderate (D2) and severe (D3) drought treatments led to negative GD values. GD decreased by 23.79%, 114.85%, and 175.50% for D1, D2, and D3 treatments, respectively, while reductions of 40.00%, 73.33%, and 90.00% in GD were observed compared to the control (CK). Pn decreased significantly across treatments, with D1<CK<D2<D3 in Ci. Stomatal limit value (Ls) and water use efficiency (WUE) followed the order: D1>CK>D2>D3. Light energy transmission to PSI by the unit reaction center (REo/RC) initially increased then decreased, significantly smaller in D3 compared to D1. Conversely, heat dissipation absorbed by the unit reaction center (DIo/RC) increased notably in D3 compared to D1 and CK. PIABS, WK, VJ, and ΔI/I0 decreased over time, while Rubisco enzyme activity decreased, while proline (Pro) levels increased. Superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and malondialdehyde (MDA) levels significantly increased during D1 treatment but decreased with D2 and D3 treatments. Overall, drought severity had varying impacts on Cinnamomum camphora growth and photosynthetic structure, with D1 treatment maintaining normal growth and metabolic activities, while D2 and D3 treatments resulted in severe membrane damage, rendering seedlings essentially unable to survive. These findings provide a theoretical basis for implementing water management practices and conservation strategies for camphor seedlings.